Seismic Performance Assessment of Masonry Buildings - Blerim Nika; Nikolla Vesho; Aguljeln Marku; Merita Guri (International Journal of Scientific Research in Civil Engineering, 2022)
In Albania, as a country with high seismic risk, seismic design and assessment of structures is very important. In most cases, the seismic design situation is crucial in structural solution and in the dimensions of elements. In addition to designing new structures seismic assessment of existing structures is an ever-increasing need due to the existence of old structures built with design codes that reflect knowledge and accumulated experiences up to the time of their design and construction. It can be said that in compared to 30 - 40 years ago, the changes in design codes are significant. The building that will be used as a case study for analyses purpose is named as type 77/11 according to the previous institute of construction. This can serve as a reference for the social masonry buildings built in the communism era before the year 1980. Before this year, the design code used was the KTP-63. The analysis will be performed with ETABS software, and for the seismic performance will be used the KTP-89 spectre and EC-8 spectre (since Albania is trying to implement this code as a national standard). For strengthening technique will be used TRM.
Keywords: Performance Point; Strengthening; TRM Material; Capacity Curve